Menggali profil dan kebutuhan guru dalam pembelajaran memirsa berbasis literasi visual - Darmawan, Hana Mumtazia Nurhaq; Anshori, Dadang S.; Mulyati, Yeti; Damaianti, Vismaia S. (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe the profile of viewing learning activities at the junior high school level and map the needs of teachers in teaching the skill. The methods used in this research are descriptive qualitative methods and literature review. Primary data in this study was obtained through a semi-open questionnaire from 42 Indonesian language teachers at the junior high school level. Meanwhile, secondary data was obtained from the analysis results in previous studies with the help of the Publish or Perish application. The result of this research is the profile of viewing skills learning conducted by teachers and on previous research. From the analysis, it was found that the viewing skills learning carried out was still very limited. The presence of these constraints highlights the necessity for creating educational resources, organized lesson plans, assessments that genuinely evaluate students’ viewing abilities and teacher training. The findings of this study can significantly contribute to the advancement of learning models or strategies, teaching modules, supplementary materials, educational websites, or the creation of evaluations focused on visual literacy-based viewing skills for students, ensuring alignment with field requirements.